2017
DOI: 10.1037/a0039993
|View full text |Cite
|
Sign up to set email alerts
|

Poly-victimization and its relationship with emotional and social adjustment in adolescence: Evidence from a national survey in Switzerland.

Abstract: Objective: The present study investigates, for the first time in a wealthy country of Central Europe, the prevalence of poly-victimization (exposure to multiple forms of victimization within the past year) in an adolescent population. It further examines associations between single victimization types (such as sexual or physical assaults) with emotional and social functioning when poly-victimization is controlled for. Method: Data from a large and near-representative national school survey in Switzerland (N ϭ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
(80 reference statements)
4
23
0
2
Order By: Relevance
“…Around the world, studies on polyvictimization report similar findings, suggesting that victimization is a norm in the lives of youth and that there is a significant population of polyvictims (Radford, Corral, Bradley & Fisher 2014;Chan 2014;Nilsson, Dahlstöm, Priebe & Svedin, 2015;Lätsch, Nett & Hümbelin, 2016). In Canada, Cyr, Clément and Chamberland (2014) studied polyvictimization among 2,800 youths aged 2 to 17 in Quebec.…”
Section: Developmental Victimologymentioning
confidence: 93%
See 2 more Smart Citations
“…Around the world, studies on polyvictimization report similar findings, suggesting that victimization is a norm in the lives of youth and that there is a significant population of polyvictims (Radford, Corral, Bradley & Fisher 2014;Chan 2014;Nilsson, Dahlstöm, Priebe & Svedin, 2015;Lätsch, Nett & Hümbelin, 2016). In Canada, Cyr, Clément and Chamberland (2014) studied polyvictimization among 2,800 youths aged 2 to 17 in Quebec.…”
Section: Developmental Victimologymentioning
confidence: 93%
“…It has been shown that childhood victimization is an explanatory factor for the presence of several mental health problems during childhood as well as into adulthood (Molnar, Buka & Kessler, 2001). For its part, polyvictimization is closely tied to a decrease in emotional well-being and social functioning, and this, more than any other individual type of victimization (Lätsch, Nett & Hümbelin, 2016). Young victims present an array of mental health problems such as depression, emotional disorders, anxiety, self-harm, substance abuse, dissociation and eating disorders (Brière and Lanktree, 2008).…”
Section: Risk Factors For Polyvictimization Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a CNN to extract the characteristics of the target being tracked is a prevalent and effective method. This approach focuses primarily on object detection and local features of the target to be used for monitoring purposes [6][7][8][9]. Qi et al [23] used two different CNN structures to distinguish the target from other distractors in the scene.…”
Section: Human Detectionmentioning
confidence: 99%
“…Most of the studies proposed in the past few years tend to answer the question: was it a sexual assault? However, few of them focus on the early detection of this crime [7,8]. Indeed, this is a difficult task, as the posture of both individuals (the rapist and the victim) might be both on the same abscissa of the camera, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%